Desenvolvimento de um durômetro portátil para madeiras com o uso de transdutor de deslocamento - Assis, Albert Augusto de [UNESP] (2015)
Hardness is considered a meaningful quality indicator for wood and correlates well with other mechanical properties of the material, like compressive strengths normal and perpendicular to the grain. Besides its good correlation to those mechanical properties, the hardness test is easier to perform than any other strength test. In Europe the most widely used method for determining wood hardness is the Brinell test, whereas in the Americas the Janka test is predominant. More recently, international studies have reported the use of dynamic hardness for wood, claiming as main advantage the feasibility of tests under field conditions. This paper presents results obtained in the development of the third generation of a portable hardness tester for wood, which uses displacement transducer and embedded electronic processor in order to automate the dynamic hardness measurement. Functional tests of the equipment carried out using eight species of Eucalyptus, revealed strong correlation to Janka hardness and the possibility of its prediction by dynamic hardness. Beyond that, the classical problems of sinking-in and recovery of the indented area where solved by the equipment using under-load measurements of indentation's depth. Furthermore, this paper introduces a new methodology for dynamic hardness calculation, which is based on the ratio between the average impulse force promoted by the indentation and its depth.